Deforestasi dan Pertumbuhan Ekonomi: Hipotesis Environmental Kuznet Curve di Pulau Kalimantan dan Pulau Sumatera - Rina Kurniawati (Jurusan Ilmu Ekonomi Universitas Katolik Parahyangan, 2022)
Deforestation is one of the environmental problems faced by Indonesia. Deforestation arise do to wood production and land conversion into oil palm plantations. Indonesia is one of the largest timber and palm oil exporters in the world market. In many cases, production of timber and palm oil often does not pay attention to the environmental damage. According to the Directorate of Inventory and Monitoring of Forest Resources (2017), the highest deforestation occurred on the islands of Kalimantan and Sumatra. This study aims to prove the Environmental Kuznet Curve hypothesis and find the effect of timber production and oil palm land on deforestation on Kalimantan Island and Sumatra Island in 2010 - 2017 using the Panel Least Square (PLS) method. The research results show that the Environmental Kuznet Curve (EKC) hypothesis is not proven and the variables of timber production and oil palm land significantly influence deforestation.